Strategi Guru Dalam Pengembangan Pola Pembelajaran Pendidikan Agama Islam Berwawasan Pendidikan Multikultural di Sekolah Dasar IT Harapan Mulia Palembang - Abd. Amri Siregar (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Teachers' strategies in developing multicultural-oriented learning patterns are not optimal, as indicated by ongoing brawls between students, inter-ethnic conflicts, and religious blasphemy. The purpose of this study was to analyze teachers' strategies in developing multicultural-oriented Islamic religious education learning patterns in schools. Using descriptive qualitative methods. The results of the study show that teacher strategies in developing Islamic religious education learning patterns with a multicultural perspective are a series of activities designed and developed by teachers in instilling values of tolerance, encouraging students to appreciate differences in culture, customs, ethnicity and religion, building an understanding of diversity and forming an Islamic personality among students. Thus it can be concluded that the teacher's strategy in developing a multicultural Islamic religious education learning pattern includes teachers providing knowledge, understanding, attitudes and actions in developing conditions of differences and similarities in gender, race, culture, customs, ethnicity and religion, and teachers are able to provide knowledge, attitudes and behavior in implementing educational interactions and social interactions based on multicultural values to students. So it can be suggested in developing a multicultural Islamic religious education learning pattern, then improve teacher strategies in schools.Keywords: Teacher Strategy, Learning Pattern Development, Multicultural Education. Abstrak: Strategi guru dalam pengembangan pola pembelajaran berwawasan multikultural belum optimal, ditandai masih terjadi tawuran antar pelajar, konflik antar etnis, dan penistaan agama. Tujuan penelitian ini untuk menganalisis strategi guru dalam pengembangan pola pembelajaran pendidikan agama Islam berwawasan pendidikan multikultural di sekolah. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa strategi guru dalam pengembangan pola pembelajaran pendidikan agama Islam berwawasan multikultural merupakan segala rangkaian kegiatan yang dirancang dan dikembangkan oleh guru dalam menanamkan nilai-nilai toleransi, mendorong peserta didik untuk menghargai perbedaan budaya, adat istiadat, etnis dan agama, membangun pemahaman tentang keberagaman serta membentuk kepribadian islami di kalangan peserta didik. Oleh karena itu, dapat disimpulkan bahwa strategi guru dalam pengembangan pola pembelajaran pendidikan agama Islam berwawasan multikultural antara lain guru memberikan pengetahuan, pemahaman, sikap dan tindakan dalam mengembangkan kondisi perbedaan jenis kelamin, ras, budaya, adat istiadat, etnik dan agama, serta memberikan pengetahuan, sikap dan perilaku dalam mengimplementasikan interaksi edukatif dan interaksi sosial berdasarkan nilai-nilai multikultural kepada peserta didik. Sehingga dapat disarankan dalam pengembangan pola pembelajaran PAI berwawasan multicultural, maka tingkatkan strategi guru di sekolah.Kata kunci: Strategi Guru, Pengembangan Pola Pembelajaran, Pendidikan Multikultural.